Preoperative circulating platelet, neutrophil, and lymphocyte counts predict survival in oral cancer. (11th February 2019) - Diao, Pengfei; Wu, Yaping; Ge, Han; Li, Jin; Zhang, Wei; Huang, Rong; Wang, Yanling; Cheng, Jie
Abstract: Objective: Circulating immune‐inflammatory cells have been increasingly recognized as robust prognostic biomarkers in cancer. Here, we sought to evaluate the prognostic values of preoperative peripheral platelet, neutrophil, lymphocyte quantitation in patients with primary oral squamous cell carcinoma (OSCC). Materials and methods: A total number of 309 patients with primary OSCC surgically treated at our institutions were retrospectively included. Detailed demographic, clinicopathological, laboratory, and follow‐up data were collected. The Kaplan–Meier analysis and Cox regression assay were performed to assess the prognostic values. A new prognostic risk score was developed and designed as PNL (platelet–neutrophil–lymphocyte) score based on combined preoperative platelets, neutrophils, and lymphocytes via calculating the regression coefficients of each type of cell by Cox regression analysis. Results: High platelet counts (≥266 × 10 9 /L), neutrophil counts (≥2.8 × 10 9 /L), PNL scores, and low lymphocyte counts (<1.4 × 10 9 /L) significantly associated with reduced overall and disease‐free survival (Kaplan–Meier, p  < 0.05, Log‐rank test). Univariate and multivariate regression analyses revealed that individual platelet, neutrophil, lymphocyte quantitation, and PNL score were independent prognostic predictors for patient survival. Moreover, receiver operating characteristics curve revealed superior prognostic utility of PNL score for OSCC. Conclusions: Our findings indicate that preoperative circulating platelets, neutrophils, lymphocytes, and PNL score serve as noninvasive, low‐cost, and powerful prognostic predictors for patients with OSCC.